Outcome of endoscopy-negative iron deficiency anemia in patients above 65: A longitudinal multicenter cohort. Issue 47 (November 2016) - Clere-Jehl, Raphaël; Sauleau, Erik; Ciuca, Stefan; Schaeffer, Mickael; Lopes, Amanda; Goichot, Bernard; Vogel, Thomas; Kaltenbach, Georges; Bouvard, Eric; Pasquali, Jean-Louis; Sereni, Daniel; Andres, Emmanuel; et al.
Abstract : Abstract: After the age of 65 years, iron deficiency anemia (IDA) requires the elimination of digestive neoplasia and is explored with upper and lower gastrointestinal (GI) endoscopy. However, such explorations are negative in 14% to 37% of patients. To further evaluate this issue, we evaluated the outcomes of patients aged over 65 years with endoscopy-negative IDA. We retrospectively analyzed the outcomes of in-patients over the age of 65 years with IDA (hemoglobin <12 g/dL and ferritin <70 μg/L) who had negative complete upper and lower GI endoscopies in 7 tertiary medical hospitals. Death, the persistence of anemia, further investigations, and the final diagnosis for IDA were analyzed after at least 12 months by calling the patients' general practitioners and using hospital records. Between 2004 and 2011, 69 patients (74% women) with a median age of 78 (interquartile range (IQR) 75–82) years and hemoglobin and ferritin levels of 8.4 (IQR 6.8–9.9) g/dL and 14 (IQR 8–27) μg/L, respectively, had endoscopy-negative IDA, and 73% of these patients received daily antithrombotics. After a follow-up of 41 ± 22 months, 23 (33%) of the patients were dead; 5 deaths were linked with the IDA, and 45 (65%) patients had persistent anemia, which was significantly associated with death ( P  = 0.007). Further investigations were performed in 45 patients; 64% of the second-look GI endoscopies led to significant changes in treatment compared with 25% for the capsule endoscopies. Conventional diagnoses of IDA were ultimately established for 19 (27%) patients and included 3 cancer patients. Among the 50 other patients, 40 (58%) had antithrombotics. In endoscopy-negative IDA over the age of 65 years, further investigations should be reserved for patients with persistent anemia, and second-look GI endoscopy should be favored. If the results of these investigations are negative, the role of antithrombotics should be considered.